Captive Management and Reproduction of the Rio Pescado Stubfoot Toad (Atelopus balios) - Chris Buttermore; Luis Daniel Navarro Gutierrez; Luis Sigler (Journal of Zoological and Botanical Gardens, 2024)
The Rio Pescado stubfoot toad (Atelopus balios) is a critically endangered member of the struggling Atelopus genus which has been ravaged by the fungal pathogen Batrachochytridium dendrobatidis. Captive management of this species is crucial to improve survival outcomes in their native range in Ecuador. Here, we talk about reproductive successes with A. balios at The Dallas World Aquarium, which represents the first successful reproduction of this species outside of Ecuador. We document five clutches of eggs that were deposited in the adult breeding tank and the developmental rates of the offspring. We also provide observations on husbandry regimes that support the recovery of the females’ postdeposition along with observed time between reproductive events for females. We also document the habitat requirements of the adults of the species and the offspring with notes on feeding practices once toadlets emerge from the water. Documentation on the reproduction of Atelopus species is critical to understanding habitat preferences and cues needed to influence reproduction in the wild and thus give insights into the path of captive propagation in the conservation of the focal species.